Analysis of reaction time and lateral displacements in national level table tennis players: are they predictive of sport performance?. (4th July 2019) - Castellar, Carlos; Pradas, Francisco; Carrasco, Luis; La Torre, Ana De; González-Jurado, José Antonio
ABSTRACT: Table tennis is a sport in which players perform technical actions at high speed. In this regard, response time (TTR), reaction time (RT) and movement time (MT) are key factors that can contribute to successful performance of table tennis players. The purposes of this study were to determine the magnitude of intra-subject and inter-subject variability in TTR based on player's lateral dominance, to establish possible differences between sex, age group and ranking position for TTR, RT and MT, and to relate these results with table tennis performance by analysing the achieved position in the national ranking. A total of 116 Spanish national level players (71 males and 45 females) carried out the Take-Off Reaction Test in a table tennis court simulating real sport conditions. There were no intra-sex differences for the total sample when lateral dominance was checked. On the other hand, male players showed lower MT than females whereas female players showed significantly lower RT values than males. Moreover, and taken into account the correlation analysis, we can conclude that both lower RT and MT can be considered as key variables of performance in table tennis.